Creative problem solving in teaching current events to fast learners (accelerated class) - Eugenio, Celia A. (College of Education, University of the Philippines Diliman, 1975)
A non-parametric study was designed to prove the null hypotheses: a) training in creative problem solving has no effect on the creative ability of fast learners in an accelerated class; b) creative problem solving has no effect on the subject matter achievement of fast learners in an accelerated class. The Wilcoxon Matched-Pairs Signed Ranks Test was employed to statistically test the magnitude and direction of the score differences. Based on the findings of the study, training in creative problem solving has an effect on the creative ability of the fast learners in an accelerated class but has no effect on the subject matter achievement.